Aprendizaje radiológico basado en problema clínico específico: linfadenopatía cervical, tips clínicos y de imagen para facilitar su tipificación. - Motta-Ramírez, Gaspar A.; Almazán-Santiago, Martha L.; Gallegos-Reséndiz, María F. (Anales de Radiologia, Mexico)
Objective: The clinical evaluation of palpable neck masses usually underestimates or overestimates their extension. A neck mass is defined as any increase in volume that forms in the cervical region, of congenital or acquired origin and that is visible, palpable, or identified by means of an imaging study. Method: An extensive bibliographic review was carried out in the PubMed database, where recent bibliographic information was inquired using the following keywords: cervical mass in adults, neck mass in adults, cervical lymphadenopathy in adults, as well as on evaluation methods such as ultrasound (US) and computed tomography, including original studies, and bibliographic reviews. Results: The manuscript indicates the CRISPS mnemonic, the CLN-RADS (Cervical Lymph Node Imaging Reporting and Data System for ultrasound of Cervical Lymphadenopathy) as well as the proposal of the UNN-RADS (Ultrasound Neck Node Reporting and Data System) classification, and how US examination of the neck should be performed with a systematic approach, organized to evaluate, and report cervical lymph nodes and do not omit any ganglionic chain. In current medical practice, there is often no defined clinical picture when a neck mass appears in adults and reflects a severe abnormality. Conclusion: A new persistent neck mass in an adult patient should be considered malignant until proven otherwise. Any neck mass, particularly unilateral, asymptomatic, in cervical lymph node group topography, should be considered a metastatic lesion, until proven otherwise.